A Rookie in Laparoscopic Liver Resections: Initial Performance of 22 Cases at Lampang Regional Hospital - Wittayachumnangul, Bun (The Thai Journal of Surgery, 2025)
Objective: To review the initial 22 cases of laparoscopic liver resections (LLRs) by a general surgeon to enhance the quality of patient care and implementation for the broader medical community in the northern region of Thailand. Materials and Methods: This descriptive retrospective study analyzes the author’s liver surgery registry data from August 2018 to December 2023. Patients included underwent LLRs for various provisional diagnoses. All received computed tomography (CT) triple-phase liver protocol scans to assess provisional diagnosis and resectability. The IWATE score was used to evaluate procedural difficulty, and inflow control techniques were identified. Results: A total of 22 patients underwent LLRs between August 2018 and December 2023, with a mean age of 63.8 ± 13.8 years; 68.2% were male. Most patients were classified as Child Turcotte Pugh (CTP) A. The most common preoperative and postoperative diagnosis was hepatocellular carcinoma (HCC). The mean IWATE score was 5.6 ± 2.2, and 40.9% of the surgeries were classified as major procedures. The most common resection was left hepatectomy, while the procedure with the highest difficulty score was anterior sectionectomy for HCC. Estimated blood loss was 125 [100, 300] milliliters, and the mean operative time was 4.1 hours ± 105.9 minutes. One patient died postoperatively due to a ruptured abdominal aortic aneurysm (rAAA). Conclusion: LLRs are feasible for surgeons with a learning curve. IWATE difficulty scoring can assist surgeons in deciding on minimally invasive surgery, albeit with some limitations.